Supervised exercise training in patients with chronic thromboembolic pulmonary hypertension as early follow-up treatment after pulmonary endarterectomy: a prospective cohort study - Nagel, Christian; Nasereddin, Mohammed; Benjamin, Nicola; Egenlauf, Benjamin; Harutyunova, Satenik; Eichstaedt, Christina; Xanthouli, Panagiota; Mayer, Eckhard; Grünig, Ekkehard; Guth, Stefan (Respiration, 2020)
Background: Data on exercise training in chronic thromboembolic pulmonary hypertension (CTEPH) after pulmonary endarterectomy (PEA) as well as data on clinical and haemodynamic changes shortly after PEA are lacking. Objective: The objective of this prospective study was to analyse the safety, feasibility, and the effectiveness of combined supervised inpatient rehabilitation in patients with CTEPH directly after PEA. Methods: CTEPH patients started a 19-week rehabilitation program (3 weeks as inpatients and continued at home for another 16 weeks) with supervised exercise training as follow-up treatment shortly after PEA. Haemodynamics were assessed by right heart catheterisation before PEA and 22 weeks after PEA. Non-invasive assessments as transthoracic echocardiography and 6-min walking distance (6MWD) were performed before PEA and after 3 (that is, beginning of rehabilitation), 6, and 22 weeks following PEA. Adverse events were recorded throughout the study. Results: Forty-five CTEPH patients were included (49% female, 57.6 ± 12.4 years old, 60% WHO functional class III). Rehabilitation was started 3.3 ± 0.9 weeks after PEA. Exercise training was well tolerated in all patients without severe side effects. Haemodynamics measured by right heart catheterisation significantly improved from pre-PEA to 22 weeks post-PEA in cardiac output (+1.2 ± 1.5 L/min, 33.4%, = 0.001) and mean pulmonary arterial pressure (-19 ± 13 mm Hg, -39.6%, p < 0.0001). Right heart size measured by echocardiography, 6MWD, quality of life, and oxygen saturation significantly improved not only within the first 3 weeks after PEA but also during the following 19 weeks of exercise training. Conclusions: Supervised exercise training was feasible as early follow-up treatment after PEA. Further controlled studies are needed to discriminate the effects of PEA and early follow-up rehabilitation. Trial Registration: The study was registered at clinicaltrials.gov (NCT01393327) on July 13, 2011. The study start date was January 2010, and completion date was December 2013.
Gesehen am 25.09.2020